Ernst & Young’s $100 Million SEC Penalty: - Blythe, Stephen Errol (Journal of Accounting, Business and Management (JABM), 2025)
The U.S. securities and exchange commission (SEC) monitors the financial reporting practices of business firms that sell stock on U.S. exchanges. The SEC requires certified public accountants (CPAs) to audit those firms in order to provide reasonable assurance that the firms’ financial statements contain no material misstatements and that the firms have good internal accounting controls. Since CPAs serve as a watchdog for the SEC, the CPA exam content should be rigorous and the exam should be securely administered; this helps to ensure that only qualified applicants become CPAs and that audits are performed competently. Accordingly, the SEC was disappointed to learn that some of the auditors at Ernst & Young (E&Y), one of the four largest international CPA firms, had cheated on CPA ethics examinations. Furthermore, E&Y management attempted to cover up the cheating. E&Y admitted its culpability and agreed to pay a $100 million penalty and undertake remedial measures to correct the firm’s ethical issues. At the end of this study, the author: (1) emphasizes the critical importance of ethical behavior to CPAs; (2) makes recommendations for avoidance of internal exam cheating at CPA firms; and (3) makes recommendations to the SEC for improvement of its enforcement quality.